Cutaneous Eruption due to Telaprevir - Eduardo Mastrangelo Marinho Falcão; Beatriz Moritz Trope; Mariana Marteleto Godinho; Leonardo Hoehl Carneiro; João Marcello de Araujo-Neto; Cristiane Alves Villela Nogueira; Marcia Ramos- (Karger Publishers, 2015)
Hepatitis C virus (HCV) chronically infects 0.5-3% of the world population. A large group of patients develop cirrhosis and its complications. Since 2011, telaprevir and boceprevir are used, improving the disease evolution. One of the main side effects of these drugs is skin eruption. We report a 53-year-old patient with cirrhosis due to HCV who started the classic treatment associated with telaprevir. In the ninth week, he presented a severe rash that required the interruption of this drug. We emphasize the importance of early recognition and appropriate management of adverse skin reaction.